(untitled) (Bangladesh Journal of Plant Taxonomy, 2021)
The Internal Transcribed Spacers (ITS) sequences of nuclear ribosomal DNA (nrDNA) are commonly used in plant molecular phylogenetics for the molecular based taxonomic identification and DNA barcoding because of shorter length and easy to amplify by using the universal primers, and further has discrimination ability to distinguish the taxon at lower taxonomic level. The present molecular phylogenetic analysis of ITS nrDNA sequences focuses to determine the taxonomic status of an unresolved medicinally important species Euphorbia schimperiana Scheele of the family Euphorbiaceae reported from Saudi Arabia. The combined length of the entire ITS region in E. schimperiana is 644 nucleotides. The study reveals that E. schimperiana shows a close proximity with the members of the subgenus Esula. Bangladesh J. Plant Taxon. 28(1): 125-130, 2021 (June)